Keanekaragaman Jenis Bambu Di Hulu Tampang Dusun Utara Kabupaten Barito Selatan Propinsi Kalimantan Tengah: Diversity of Bamboo species in Hulu Tampang Dusun Utara Districts South Barito Regency Central Kalimantan Province - Agus Sadono; Nuriman Wijaya (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2022)
Bamboo is one of the results of a non-timber forest that grows in the secondary forest and open forest who be found in Hulu Tampang Dusun Utara area. The purpose of this research is to know diversity of bamboo species in the area Hulu Tampang Dusun Utara South Barito Regency, Central Kalimantan. This research was conducted in Hulu Tampang Dusun Utara, during one month then continued by analysis of data. The collection of bamboo data at the research site is conducted by the cruising method by walking down the path. Results showed in Hulu Tampang Dusun Utara there are 5 species of bamboo had been found consisting of 4 different genera namely Bambu madintang (Bambusa vulgaris), Bambu petung (Dendrocalamu asper), Bambu Tamiang (Schizostachyum blumei), Bambu Jawa (Gygantocla atter) and Bambu Cina/ Bambu Pagar (Bambusa multiplex)